Aerodynamic analysis of cylinder to flat plate (CyFlap) embedment for agriculture purposes - Azman, Sara Wajiha; Mohd Rafie, Azmin Shakrine; Gires, Ezanee (Aeronautical and Astronautical Society of the Republic of China, Taiwan, 2024)
The goal of this research study is to conduct aerodynamic analysis for the agricultural Cylinder to Flat Plate (CyFlap) embedment that exploits the principle of Magnus effects. This study is motivated by the widespread usage of quadrotor UAVs in contemporary agriculture, which produces a downwash effect that can harm the plants. In conjunction to this, it is believed that the application of the proposed AgroCyFlaP can help to alleviate this problem. In short, the presented research work in this paper essentially covers the process of developing, manufacturing, analyzing and also wind tunnel testing of the design concept. All in all, the findings show that the proposed AgroCyFlaP demonstrates a substantial lift force around 60% more at the condition of 15º angle of attack, enabling it to transport weights that are comparable to a base UAV but without creating the downwash impact, unlike conventional rotorcraft. Although the AgroCyFlaP has shown good potential for the agricultural applications, further study is still needed to improve its aerodynamics and operation for practical implementation in the real world.